Peripheral DNA Methylation of Cortisol- and Serotonin-Related Genes Predicts Hippocampal Volume in a Pediatric Population - Taena Hanson; Sophia Spencer; Samantha A. Harker; Fatoumata Barry; Phoebe Burton; Jennifer Beauchemin; Sarah E. Mennenga; B. Blair Braden; Viren D'Sa; Daphne Koinis-Mitchell; Sean C.L. Deoni; Candace R. Lewis (Biological Psychiatry Global Open Science)
Background: Hippocampal volume increases throughout early development and is an important indicator of cognitive abilities and mental health. However, hippocampal development is highly vulnerable to exposures during development, as seen by smaller hippocampal volume and differential epigenetic programming in genes implicated in mental health. However, few studies have investigated hippocampal volume in relation to the peripheral epigenome across development, and even less is known about potential genetic moderators. Therefore, in this study, we explored relationships between hippocampal volume and peripheral DNA methylation of mental health–related genes, specifically NR3C1, FKBP5, and SLC6A4, throughout early development and whether these associations were moderated by age or genotype. Methods: Bilateral hippocampal volume was computed from T2-weighted images through FreeSurfer, and DNA methylation was measured from saliva using the Illumina MethylationEPIC microarray in a pediatric population (N = 248, females = 112, meanage = 5.13 years, SDage = 3.60 years). Results: Multiple linear regression and bootstrapping analyses revealed that DNA methylation of NR3C1, FKBP5, and SLC6A4 was associated with hippocampal volume and that these relationships were moderated by age and gene-specific variants. Conclusions: These findings support the validity of peripheral DNA methylation profiles for indirectly assessing hippocampal volume and development and underscore the importance of genotype and age considerations in research. Therefore, peripheral epigenetic profiles may be a promising avenue for investigating the impacts of early-life stress on brain structure and subsequent mental health outcomes.